International Commercial Arbitration and the Possible Application Thereof in Iraq - الموسوي, علي فوزي (Journal of Legal Sciences, 2019)
International commercial arbitration is a special judicial system based primarily on an agreement, be it an arbitration clause or an arbitration agreement (compromise), betweenparties to a dispute. It is therefore a system aiming at settling commercial disputes by submitting them to a single arbitrator, or an arbitral panel, or an arbitral tribunal (e. g. , theInternational Court of Arbitration). It is therefore also a means for settling an existing or future dispute that entails refraining from resorting to the competent judiciary. It is alsoan extra – judicial action aiming at establishing justice between people. The aim of arbitration is to bring justice to parties in conflict, but it is also designed to preserve peaceamong them, by providing solutions that are deemed satisfactory by each party, and through direct confrontation. It is a technical means for peaceful cooperation betweencountries with different systems. Resorting to international commercial arbitration is intended to solve a dispute based on a desire for reconciliation, to thereby avoid privateretribution, without waiving the protection of the law, although it does entail waiver of state judges’ jurisdiction to rule over the dispute, since the parties choose their ownjudge.This type of Arbitration is called “international” if it relates to international commercial interests. Arbitration is also used in other areas, e. g. , personal status and tribal arbitrationin Iraq. However, our study concentrates on international commercial arbitration and the possible application thereof in Iraq.